Do Implicit Motives Influence Perceived Chronic Stress and Vital Exhaustion? - Schoch, Jessica; Noser, Emilou; Ehlert, Ulrike (Frontiers in Psychology, 2018)
Vital exhaustion (VE) results from the experience of chronic stress. However, research on stress types and their relation to VE is rare. Moreover, the role of implicit motives in these processes has not yet been investigated. Analysis included 101 vitally exhausted men aged 40-65 years. Participants provided self-report data on their experience of chronic stress and social support. Subtypes of work-related and social stress were positively associated with VE. Implicit affiliation and achievement were linked to social support and chronic stress, and indirectly to VE. Moreover, they moderated the relationship between stress and exhaustion. In conclusion, implicit motives are key factors in the stress process: They are involved in an individual’s experience of stress and stress-related consequences for mental health.